2018
DOI: 10.1177/0192513x18755196
|View full text |Cite
|
Sign up to set email alerts
|

Daughters’ and Sons’ Remittances in Rural China: Findings From a National Survey

Abstract: In China, it has historically been the responsibility of sons rather than daughters to provide economic support to older parents. This study used a sample of 12,389 non-coresident children to analyze whether such gender differences persist in contemporary rural China and how they can be explained. A two-part model showed that daughters were somewhat more likely to remit to parents, although sons provided higher amounts. The support of parents by both daughters and sons was found to be strongly related to out-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 46 publications
1
26
2
Order By: Relevance
“…To our knowledge, this is the first study to provide such a comprehensive overview of intergenerational proximity in the Chinese context. Contrary to recent reports of increasing gender equality in other aspects of intergenerational solidarity (Gruijters, , ; A. Hu, ; Xie & Zhu, ), we find that residential decisions of Chinese couples continue to exhibit a strong bias toward the husband's parents. There is, however, a social gradient in patrilocality, and neolocal residence is the modal arrangement among high‐status couples.…”
Section: Introductioncontrasting
confidence: 99%
“…To our knowledge, this is the first study to provide such a comprehensive overview of intergenerational proximity in the Chinese context. Contrary to recent reports of increasing gender equality in other aspects of intergenerational solidarity (Gruijters, , ; A. Hu, ; Xie & Zhu, ), we find that residential decisions of Chinese couples continue to exhibit a strong bias toward the husband's parents. There is, however, a social gradient in patrilocality, and neolocal residence is the modal arrangement among high‐status couples.…”
Section: Introductioncontrasting
confidence: 99%
“…Contrary to recent reports of increasing gender equality in other aspects of intergenerational solidarity (Gruijters, 2017(Gruijters, , 2018A. Hu, 2017;Xie & Zhu, 2009), we find that residential decisions of Chinese couples continue to exhibit a strong bias towards the husband's parents.…”
Section: Introductioncontrasting
confidence: 99%
“…This is perhaps because parents of only daughters usually hold more egalitarian gender role attitudes given that they had stopped giving birth in the case of having no sons. Moreover, recent studies have found that it is increasingly becoming common for daughters to transfer money or provide care to their aging parents in both rural and urban China ( Xie and Zhu, 2009 ; Gruijters, 2018 ). Thus, modern parents have economic incentives to invest in their only daughters ( Tsui and Rich, 2002 ).…”
Section: Discussionmentioning
confidence: 99%